MINERAL RESOURCES OF UZBEKISTAN AND THEIR GLOBAL IMPORTANCE - Teshaboyeva Nafisa Zubaydulla qizi; Baxtiyarova Dilrabo Hikmatillo qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Uzbekistan is one of the richest countries in Central Asia in terms of mineral resources. The nation hosts extensive deposits of gold, uranium, natural gas, oil, copper, coal, phosphorites, and various industrial minerals such as limestone, marble, granite, and bentonite clay. These resources are critical not only for national economic growth but also for international markets, supporting global industries like energy production, metallurgy, agriculture, construction, and high technology. Additionally, the country’s rich ecological reserves and national parks, including Chatkal, Zaamin, and Nuratau–Kyzylkum, contribute to sustainable resource management and environmental protection. This paper examines the geological and economic significance of Uzbekistan’s mineral wealth and its growing strategic importance in the global context.